2022
DOI: 10.1002/ijc.34186
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation biomarkers in colorectal cancer: Clinical applications for precision medicine

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer death worldwide that is attributed to gradual long‐term accumulation of both genetic and epigenetic changes. To reduce the mortality rate of CRC and to improve treatment efficacy, it will be important to develop accurate noninvasive diagnostic tests for screening, acute and personalized diagnosis. Epigenetic changes such as DNA methylation play an important role in the development and progression of CRC. Over the last decade, a panel of DNA methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 146 publications
(277 reference statements)
0
9
0
Order By: Relevance
“…Stool is utilized in biomarker studies in intestinal diseases because of the relative ease and non-invasive nature of sample acquisition; however, examining methylation patterns in stool can be technically challenging because of the abundance of bacterial DNA and the cellular degradation that occurs during passage through the intestinal tract. Despite these challenges, studies have identified altered methylation patterns in intestinal diseases such as CRC (Refs 108, 109, 110). In addition, stool DNA methylation testing in patients with IBD has been found to detect CRC and advanced precancerous lesions (Refs 111, 112).…”
Section: Methylation Patterns As Biomarkersmentioning
confidence: 99%
“…Stool is utilized in biomarker studies in intestinal diseases because of the relative ease and non-invasive nature of sample acquisition; however, examining methylation patterns in stool can be technically challenging because of the abundance of bacterial DNA and the cellular degradation that occurs during passage through the intestinal tract. Despite these challenges, studies have identified altered methylation patterns in intestinal diseases such as CRC (Refs 108, 109, 110). In addition, stool DNA methylation testing in patients with IBD has been found to detect CRC and advanced precancerous lesions (Refs 111, 112).…”
Section: Methylation Patterns As Biomarkersmentioning
confidence: 99%
“…Furthermore, combination of epigenetic therapy and immunotherapy for CRC is very promising. Candidate DNA methylation markers for prediction can reduce resistance to therapies and evaluate patient suitability for targeted therapy [ 120 ]. Epigenetic modifiers can alter the immunogenicity of the tumor microenvironment and enhance the effects of immunotherapy and immune checkpoint inhibitors [ 121 ].…”
Section: Candidate Dna Methylation Biomarkers For Therapy and Therapy...mentioning
confidence: 99%
“…To date, several potential blood-based DNA methylation biomarkers have been identified for CRC detection, including BCAT1, BMP3, C9orf50, CDKN2A, CLIP4, KCNQ5, MLH1, NDRG4, PRIMA1, SDC2, SEPT9, SFRP2 , and VIM 2 , 4 ( Table 1 ). In fact, the best-known blood epigenetic marker for CRC is SEPT9 .…”
Section: Clinical Applications Of Dna Methylation Biomarkers For Dete...mentioning
confidence: 99%